MECHANISM OF STATE MANAGEMENT OF PRESCHOOL EDUCATION: THEORETICAL ASPECTS - Omelchenko , M. (Theory and Practice of Public Administration, 2020)
The modern education system in Ukraine has been reforming for decades. And there is no wonder, education is that industry of civilized society life which will demand continuous updating and changes. For this purpose, the Child Development Program “I am in the World” is introduced, the Concept development in preschool children is developed. These regulations are aimed at organizational and managerial changes, necessary preschool, improvement of organization forms and teaching’s diversification methods and children’s upbringing in the context of a personally oriented educational paradigm. It defines importance of a finding of quality management’s effective mechanisms of establishment’s preschool formation. Thus, mechanisms of the government represent the government’s complex system, which structure are management’s specific mechanisms (economic, motivational, political, legal, etc.) which are in aggregate capable to provide the balanced and effective functioning of government’s unique machinery. The public administration mechanisms of development preschool education can be identified as animating the public institutional mechanisms which in the form of an organizational and regulated interaction between the center and Management objects provide for the development of the pedagogical staff, content, environment, evaluation, determination of educational policy and management, the preschool education institutions system financing and procedural mechanisms of organizational, legal, economic, political nature, the priority of which is caused by functions of the preschool education system, and their effectiveness is determined by the human capital level of participants in the educational process.